The problem of religious spiritualism in humanist educational philosophy in Peru - Ayerbe Pacheco, Israel E. (2024)
This article first analyzed the influence of religious spiritualism in Peruvian education, from before independence to the present. Educational humanism was later defined as a philosophy that seeks the integral formation of the human being in academic and moral aspects. It was then argued that the concept of "spirit" as a representation of the human essence is a fiction that hinders the development of moral and academic competencies, in addition to hindering interculturality due to the dogmatic influence of Catholicism. Subsequently, the idea of God was refuted and agnosticism was proposed as the most appropriate position when referring to something transcendental. Finally, it was suggested that philosophy and ethics can fill the void left by religious spiritualism more appropriately and correctly in humanistic educational philosophy. In this article we have used the analytical hermeneutic methodology for a better understanding of the topic.